PERCEPTIONS OF LECTURERS AND STUDENTS TOWARDS THE ONLINE LEARNING PROCESS IN THE SPECIAL REGION OF YOGYAKARTA - Anastasia Susty Ambarriani; MG. Fitria Harjanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to investigate the perceptions of lecturers and students towards the online learning method. Lecturers' perceptions of the online learning process are revealed through the perspective of (1) their readiness towards the online learning process, (2) the essence of the material; (3) the students' response, and (4) online learning facilities. Meanwhile, the students' perceptions of the online learning method are depicted from their (1) adaptability; (2) lesson understanding; (3) preference for online learning, and (4) supporting facilities. The results of the study explain that lecturers and students do not experience any significant difficulties in the online learning method during the pandemic. Although they did not encounter any significant difficulties, lecturers and students still preferred face-to-face interaction compared to online learning. The difficulty of online learning faced by lecturers and students is more because of the limited communication network caused by the limited internet access Keywords: Covid-19 pandemic, the higher education learning method